Adenocarcinoma of the Stomach in Celiac Disease - Patricia J. Westlake; Lorne M. Price; James K. Kelly (Canadian Journal of Gastroenterology)
A case of adenocarcinoma of the gastric antrum in a woman with celiac disease of 21 years duration is presented. There was widespread intestinal metaplasia of the gastric antrum but the patient did not have typc A gastritis or dermatitis herpetiformis. Previous studies have shown that some patients with celiac disease have fundal gastritis but the natural history or premalignant potential of this lesion is not well described. The gastric mucosa deserves more attention in celiac disease.